Relationships of Parental Involvement to Students’ Mathematics Attitude and Performance - Richel B. Rabas Rabas; Rocel A. Turco; Ramir G. Pacheco (Future Science / FSH-PH Publications, 2026)
Parental involvement remains an underexplored factor in understanding students’ attitudes and performance in mathematics at the tertiary level. This study aimed to explore the relationships of parental involvement to students’ mathematics attitude and performance. Utilizing a descriptive-correlational research design, data were gathered from 142 first-year students at Dr. Emilio B. Espinosa Sr. Memorial State College of Agriculture and Technology (DEBESMSCAT) Cawayan Campus through the Parental Involvement Scale and the Students’ Attitude Towards Mathematics Questionnaire. Descriptive statistics and Spearman's rank correlation coefficient were used to analyze the data. Findings showed that parental involvement among respondents was at a moderate level (M=12.81), students exhibited a neutral attitude towards mathematics (M=3.31), and their performance in the subject was good (M = 87.8). The analysis did not reveal a significant correlation between the level of parental involvement and students’ attitudes towards mathematics ( p= .41). However, a significant positive correlation was identified between parental involvement and students’ performance in mathematics ( .23, p= .01). In light of these findings, the study suggests that to improve students' performance in mathematics, parents may adopt a supportive role that also encourages independence. Educators are encouraged to implement engaging, student-centered teaching methods, while schools should enhance communication and involvement initiatives between parents and teachers. Future research is recommended to explore additional factors that may affect students’ attitudes and academic success in mathematics.